2020
DOI: 10.1088/1742-6596/1651/1/012188
|View full text |Cite
|
Sign up to set email alerts
|

Multi-feature fatigue driving detection based on computer vision

Abstract: Fatigue driving is one of the main causes of traffic accidents. This paper proposes a fatigue detection method based on computer vision. The first is the introduction of an optimized algorithm, based on AdaBoost, to detect the face area, and then the ERT algorithm is used to achieve precise localization of the facial landmarks. Finally, a variety of fatigue features of eyes and mouth state associated with driving fatigue are extracted, and after the fusion of all these features, the fatigue driving detection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The combined feature showed 100% accuracy in the results. Another threshold-based model [24] proposes link rate and yawn counts. Where fatigue detection is done by multi-feature weighted sum for fatigue state recognition in which different weights were assigned to different factors.…”
Section: A Thresholding-based Techniquesmentioning
confidence: 99%
“…The combined feature showed 100% accuracy in the results. Another threshold-based model [24] proposes link rate and yawn counts. Where fatigue detection is done by multi-feature weighted sum for fatigue state recognition in which different weights were assigned to different factors.…”
Section: A Thresholding-based Techniquesmentioning
confidence: 99%
“…5. The world coordinate system to camera coordinate system transformation is shown in formula (7), the camera coordinate system to pixel coordinate system transformation and the relation between world and pixel coordinates are shown in formulas ( 8) and ( 9), and formula ( 9) can be solved iteratively by a combination of least squares and direct linear transformation, where the least squares objective function is shown in formula (10), without " ^ " for measured values and with " ^ " for predicted values.…”
Section: ) Head Pose Feature Extractionmentioning
confidence: 99%
“…For the past few years, the rapid development of image processing fields such as target detection [1][2], target tracking [3][4] and face recognition [5][6] has prompted domestic and foreign scholars to conduct in-depth research on the detection of abnormal driving behavior. Huang J et al used AdaBoots' algorithm for optimal detection of facial regions, fusing eyes and mouth features for fatigue determination, and found that the multi-feature detection is more accurate than the single feature detection [7]. Feng et al established the dataset of driver's facial feature points through MTCNN, trained the convolutional neural network, determined the driving fatigue based on the characteristic coordinates of the eyes, and solved the matter of low precision of the single target fatigue detection method in complex driving scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…However, too many subjective factors probably lead to inaccurate results. The objective evaluation methods are divided into three categories, namely, detection based on driver physiological parameters [4][5][6][7][8], detection based on vehicle behavior [9,10], and detection based on computer vision [11][12][13][14][15][16][17][18][19][20]. The detection based on driver physiological parameters, including electroencephalogram (EEG), electrocardiogram (ECG), electromyography (EMG), electrooculogram (EOG), and other parameters, can reflect the driver's physiological state.…”
Section: Introductionmentioning
confidence: 99%